Reservoir Operations to Mitigate Drought Effects With a Hedging Policy Triggered by the Drought Prevention Limiting Water Level. Issue 2 (1st February 2019) - Chang, Jianxia; Guo, Aijun; Wang, Yimin; Ha, Yanping; Zhang, Ran; Xue, Lu; Tu, Ziqian
Abstract: Severe drought events worldwide have considerably unfavorable effects on social and economic development. This paper proposes a hedging policy triggered by the seasonal drought prevention limiting water level (DPLWL) for reservoir operations during a drought event. By using this hedging policy, water resources managers can determine operating policies for drought emergence management according to specific drought conditions. A modeling framework that determines the seasonal DPLWL under different drought conditions is developed based on long‐term hydrological and meteorological information and optimal reservoir operation schemes. In particular, Fisher's optimal partitioning algorithm is applied to identifying the seasonality of the DPLWL based on hydroclimatological factors and reservoir storage conditions. The multireservoir system in the Yellow River Basin is used as a case study to assess the performance of the hedging policy triggered by DPLWLs. The results show that DPLWL has a significant advantage over the standard reservoir operation rules when dealing with multireservoir operation for drought mitigation. Plain Language Summary: Droughts, which can be a creeping disaster, can cause both natural environmental and social damage. This paper first proposes a hedging policy triggered by the drought prevention limiting water level (DPLWL) for reservoir operations to mitigate drought impacts. Furthermore, a new framework is developed to determine seasonal DPLWLs. This framework is applied to the Yellow River Basin, of which the water flow is regulated by a series of large reservoirs. This study extends the literature on hedging rules for reservoir operation by proposing a new methodology coupled with the DPLWLs, the multivariate integrated drought index (MIDI), and a reservoir operation model. The proposed approach is of great significance for decision makers in water resources management during droughts, particularly in the context of global warming. Key Points: The drought prevention limiting water level (DPLWL) is proposed as a critical condition for reservoir operation to mitigate drought impacts A new modeling framework is developed to identify DPLWLs under different drought conditions Combining DPLWLs with hedging rules decreases water shortage during extreme drought events